Practical implementation of spectral-intensity dispersion-canceled optical coherence tomography with artifact suppression. (26th March 2018) - Shirai, Tomohiro; Friberg, Ari T
Abstract: Dispersion-canceled optical coherence tomography (OCT) based on spectral intensity interferometry was devised as a classical counterpart of quantum OCT to enhance the basic performance of conventional OCT. In this paper, we demonstrate experimentally that an alternative method of realizing this kind of OCT by means of two optical fiber couplers and a single spectrometer is a more practical and reliable option than the existing methods proposed previously. Furthermore, we develop a recipe for reducing multiple artifacts simultaneously on the basis of simple averaging and verify experimentally that it works successfully in the sense that all the artifacts are mitigated effectively and only the true signals carrying structural information about the sample survive.